Tari Wrrdhining Endek - Kusuma, Putu Werdhi; Trisnawati, Trisnawati; Suartini, Ni Wayan (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2024)
The Wrrdhining Endek dance work is a new dance creation inspired by the development of typical Balinese woven cloth, namely endek cloth, which was developed by the creator with his creativity and imagination. The process of creating this dance work uses the Alma M. Hawkins method whose stages consist of an exploration stage, an improvisation stage, a forming stage and packaged into a new creative dance form danced by six dancers including three male dancers and three female dancers with a duration of 11 minutes 50 seconds. Wrrdhining Endek Dance make-up uses minimalist dance make-up to clarify the character that you want to highlight. By creating the Wrrdhining Endek Dance Work, the creator hopes that all people, especially on the island of Bali, will be proud and be able to take better care of the traditional cloth that we have, namely Endek cloth, because we have endek cloth, we wear it and we are proud. And the creator hopes that in the future the relationship between the creator and the Gumiart Bali Art Studio can remain good and collaborate again.